Neutrophils under the microscope: neutrophil dynamics in infection, inflammation, and cancer revealed using intravital imaging - Yam, Andrew O.; Jakovija, Arnolda; Gatt, Catherine; Chtanova, Tatyana (Frontiers in Immunology, 2024)
Neutrophils rapidly respond to inflammation resulting from infection, injury, and cancer. Intravital microscopy (IVM) has significantly advanced our understanding of neutrophil behavior, enabling real-time visualization of their migration, interactions with pathogens, and coordination of immune responses. This review delves into the insights provided by IVM studies on neutrophil dynamics in various inflammatory contexts. We also examine the dual role of neutrophils in tumor microenvironments, where they can either facilitate or hinder cancer progression. Finally, we highlight how computational modeling techniques, especially agent-based modeling, complement experimental data by elucidating neutrophil kinetics at the level of individual cells as well as their collective behavior. Understanding the role of neutrophils in health and disease is essential for developing new strategies for combating infection, inflammation and cancer.